U.S. advanced and novel accelerator beam test facilities. (1st May 2022) - Clarke, C.; Esarey, E.; Geddes, C.; Hofstaetter, G.; Hogan, M.J.; Nagaitsev, S.; Palmer, M.; Piot, P.; Power, J.; Schroeder, C.; Umstadter, D.; Vafaei-Najafabadi, N.; et al.
Abstract: Demonstrating the viability of Advanced Accelerator Concepts (AAC) relies on experimental validation. Over the last three decades, the U.S. has maintained a portfolio of advanced and novel accelerator test facilities to support research critical to AAC. The facilities have enabled pioneering developments in a wide variety of beam and accelerator physics, including plasma-wakefield and structure-wakefield acceleration. This paper provides an overview of the current portfolio of U.S. facilities possessing charged particle drive beams with high energies, on the order of tens of joules per pulse, or drive lasers with high peak powers, on the order of a petawatt, and are actively conducting AAC research.